SPECIFIC ASPECTS OF PREPARATION OF SEGMENTAL CASH FLOW STATEMENTS OF REGIONAL ELECTRIC NETWORKS ENTERPRISES ON THE BASIS OF INTERNATIONAL STANDARDS (International Congress on Economics, Management and Business Studies, 2026)
In this thesis, a segment cash flow statement model has been developed for JSC "Regional Electric Networks" and its 14 structural divisions in accordance with IFRS 8 "Operating Segments".
Keywords: segment reporting, IFRS 8, cash flows, reportable segment, internal flow elimination, IFRS 10, IAS 27, HET JSC, natural monopoly, territorial divisions.